Chondrocytes Derived From Mesenchymal Stromal Cells and Induced Pluripotent Cells of Patients With Familial Osteochondritis Dissecans Exhibit an Endoplasmic Reticulum Stress Response and Defective Matrix Assembly. (7th July 2016) - Xu, Maojia; Stattin, Eva-Lena; Shaw, Georgina; Heinegård, Dick; Sullivan, Gareth; Wilmut, Ian; Colman, Alan; Önnerfjord, Patrik; Khabut, Areej; Aspberg, Anders; Dockery, Peter; Hardingham, Timothy; et al.
Abstract : Bone marrow-derived mesenchymal stromal cells (BM-MSCs) and induced pluripotent stem cells (iPSCs) from patients with familial osteochondritis dissecans (FOCD) were studied. Chondrogenic pellets had poor structural integrity but were rich in glycosaminoglycan. Large amounts of aggrecan accumulated within the endoplasmic reticulum of chondrocytes, with a marked absence of aggrecan in the extracellular matrix. Matrix synthesis and assembly were globally dysregulated. These results suggest that FOCD is a chondrocyte aggrecanosis with associated matrix dysregulation. Abstract : : Familial osteochondritis dissecans (FOCD) is an inherited skeletal defect characterized by the development of large cartilage lesions in multiple joints, short stature, and early onset of severe osteoarthritis. It is associated with a heterozygous mutation in the ACAN gene, resulting in a Val-Met replacement in the C-type lectin domain of aggrecan. To understand the cellular pathogenesis of this condition, we studied the chondrogenic differentiation of patient bone marrow mesenchymal stromal cells (BM-MSCs). We also looked at cartilage derived from induced pluripotent stem cells (iPSCs) generated from patient fibroblasts. Our results revealed several characteristics of the differentiated chondrocytes that help to explain the disease phenotype and susceptibility to cartilage injury. First, patient chondrogenic pellets had poor structural integrity but were rich in glycosaminoglycan. Second, it was evident that large amounts of aggrecan accumulated within the endoplasmic reticulum of chondrocytes differentiated from both BM-MSCs and iPSCs. In turn, there was a marked absence of aggrecan in the extracellular matrix. Third, it was evident that matrix synthesis and assembly were globally dysregulated. These results highlight some of the abnormal aspects of chondrogenesis in these patient cells and help to explain the underlying cellular pathology. The results suggest that FOCD is a chondrocyte aggrecanosis with associated matrix dysregulation. The work provides a new in vitro model of osteoarthritis and cartilage degeneration based on the use of iPSCs and highlights how insights into disease phenotype and pathogenesis can be uncovered by studying differentiation of patient stem cells. Significance : The isolation and study of patient stem cells and the development of methods for the generation of iPSCs have opened up exciting opportunities in understanding causes and exploring new treatments for major diseases. This technology was used to unravel the cellular phenotype in a severe form of inherited osteoarthritis, termed familial osteochondritis dissecans. The phenotypic abnormalities that give rise to cartilage lesions in these patients were able to be described via the generation of chondrocytes from bone marrow-derived mesenchymal stromal cells and iPSCs, illustrating the extraordinary value of these approaches in disease modeling.